PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, HARGA, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA ALFAMART POOL BINA MARGA DI KOTA BOGOR - heirunissa heirunissa; Jhonson Sitanggang (Jurnal Ekonomi dan Bisnis Indonesia, 2025)
The rapid development of minimarkets in every corner of the region has given rise to quite tight competition. The purpose of this study is to determine and analyze the influence of product quality, service quality, price and location on purchasing decisions at Alfamart Pool Binamarga in Bogor City. This type of research uses a quantitative approach and data collection using a questionnaire. Sample selection was carried out using the Rao Purba Technique with a total of 100 respondents, namely buyers at Alfamart Pool Binamarga Bogor City with a non-probability sampling method. Data analysis used multiple linear regression with the help of the SPSS 26 application. The classical assumption tests used are the normality test, multicollinearity test, and heteroscedasticity test. The results of the study show that simultaneously product quality, service quality, price, and location have a significant effect on purchasing decisions at Alfamart Pool Binamarga in Bogor City. Partially, product quality, service quality, and location have a significant effect on purchasing decisions, but price does not have a significant effect on purchasing decisions at Alfamart Pool Binamarga Bogor City. The results of the calculation of the coefficient of determination show that the influence of product quality, service quality, price, and location on purchasing decisions is 80.6%, while the remaining 19.4% is influenced by other factors that are not examined in the model of purchasing decisions at Alfamart Pool Binamarga, Bogor City.